APLIKASI TEPUNG KOMPOSIT MOCAF-GARUT-KACANG MERAH PADA PRODUK MUFFIN DENGAN VARIASI JENIS GULA - Widanti, Yannie Asrie; Karyantina, Merkuria; Atrilania Sri K, Widasari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p13, 2019)
Muffin is a type of cake made from wheat flour and has a sweet taste. The use of a combination of mocaf flour, arrowroot flour and red beans is expected to provide an alternative substitute for wheat flour that is non-gluten, high in protein and high in fiber. The variations of sweeteners used in this study were granulated sugar, palm sugar and diet sugar. The results of this study indicate that the ratio of mocaf flour: arrowroot flour: red bean flour 60:30:10 with variations in the type of granulated sugar has a higher protein content of 10.15% and a ratio of 60:30:10 diet sugar has a high fiber content of 17.26%. The best available carbohydrates and calorie values of muffins are at a ratio of 60:30:10 and 40:30:30 with the addition of diet sugar respectively 30.27%, 326.84 kcal, 33.09 and 329.56 kcal. Panelists' preference for a ratio of 40:30:30 granulated sugar with a color value of 2.71 (pale yellow); mocaf flavor 2.59 (mocaf is quite pronounced); red bean flour flavor 2.78 (slight red bean flavor); soft texture 3.25 (soft); soft texture 3.01 (soft); off flavor 2.62 (slightly bitter); aftertaste 2.91 (slightly fatty in the mouth) and overall liking 2.89 (quite like the product).